Probabilistic model of slope mass movement susceptibility - a case study of Bovec municipality, Slovenia - Komac, Marko (Geologija, 2005)
A probabilistic model of slope mass movement susceptibility for the Bovec municipality in north-western Slovenia was developed based on the expert geohazard map at scale 1 : 25.000 and several other relevant influence factors. For analytical purposes 10816 models were developed, 3142 for landslide susceptibility and 7674 for rockfall susceptibility. In both cases geology / lithology and slope angle showed to be the most important influence factors. Regarding landslides, additional important factors were land use and synchronism of strata bedding and slope aspect, and in the case of rockfalls additional important factor was synchronism of strata bedding and slope aspect.